Analisis Gizi Olahan Dari Sayuran Pakis Sebagai Potensi Daerah - Wiwik _ Indrayeni; Ezi Anggraini; Wirnelis Syarif (JURNAL PENDIDIKAN DAN KELUARGA, 2020)
Based on preliminary observations, fern is a plant that has mucus, contains a lot of liquid and is easily blackened. Therefore all this time, fern vegetables cannot be processed with various kinds of preparations. Vegetable fern can only be processed for clear vegetables and rendang only by the community, while vegetable ferns are often found in areas in Indonesia, especially in West Sumatra. Based on these observations, food preparations made from vegetable ferns were accepted and liked by the community, as well as souvenirs from various regions producing ferns. The purpose of this study is to vary the variety of processed from vegetable ferns and see the level of community preference for food preparations on vegetable ferns. In this study a nutritional analysis was done through a proximate test to see the nutritional content (Carbohydrates, Protein, Water and Fat) in the products produced. The expected results in this study are the products produced have good nutritional value and are suitable for public consumption